Manhaj Wasatiyyah dalam Membangunkan Perpaduan Nasional Negara Menurut Neraca Ahli Sunnah Wal Jamaah: Wasatiyyah Method in Developing the National Unity of the Country According to Ahli Sunnah Wal Jamaah Method - Saiman, Muhamad Zuhaili (Jurnal Usuluddin, 2023)
Malaysia is a country that is based on a plural society with the differences of races and religions followers. Islam and the Malays are pillars of the country based on provisions in the Constitution through Article 3 (1) that Islam is the Federal religion. The Islam that is intended in the Constitution is based on the Ahli Sunnah Wal Jamaah method. The challenge of the country's national unity is when the reality in Malaysia practices an integration system where the minority maintain their cultural identity while living with the majority or dominant race, namely the Malays and Muslims. The objective of the study is to analyze the Wasatiyyah method in developing the national unity of the country according to the Ahli Sunnah Wal Jamaah method. The methodology used in this study is a qualitative method through library research by referring to theses, journals, newspapers and also scientific books that are related to the research topic. Based on the analysis carried out, the author found that manhaj wasatiyyah is the best approach in creating harmony among Malaysians of various races and religions to develop the country's national unity. This Wasatiyyah method coincides with the Ahli Sunnah Wal Jamaah method to ensure that Islam and the Malays become pillars of this unity based on the historical reality and identity of Malaysia.